2012
DOI: 10.2478/s11686-012-0036-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of Diphyllobothrium latum and a brief review of diphyllobothriosis in China

Abstract: Two tapeworm specimens collected in northeast China in 2009 and 2011 were identified as Diphyllobothrium latum based on morphological criteria. Molecular methods were used to confirm their identity and analyze genetic variations compared with published data for this species. Species identity was confirmed by molecular characterization of the 18S rDNA partial sequence, complete sequences of internal transcribed spacers (ITSs) and 5.8S rDNA, and partial sequences of mitochondrial cytochrome c oxidase subunit 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…PCR followed by sequencing using universal primers to amplify the ribosomal ITS1, ITS2, 5.8S, and SSU rDNA sequences or mitochondrial genes is used to identify and confirm the species identity of tapeworms found in individual cases as well as interspecies variation to construct phylogenetic relationships (408)(409)(410)(411). Sequence analysis of the ITS1, cox1, and paramyosin gene sequences from H. nana isolates from northwest Australia provided genetic support that the life cycle involves mainly humanto-human transmission (412).…”
Section: Cestodesmentioning
confidence: 99%
“…PCR followed by sequencing using universal primers to amplify the ribosomal ITS1, ITS2, 5.8S, and SSU rDNA sequences or mitochondrial genes is used to identify and confirm the species identity of tapeworms found in individual cases as well as interspecies variation to construct phylogenetic relationships (408)(409)(410)(411). Sequence analysis of the ITS1, cox1, and paramyosin gene sequences from H. nana isolates from northwest Australia provided genetic support that the life cycle involves mainly humanto-human transmission (412).…”
Section: Cestodesmentioning
confidence: 99%
“…Because of the morphologic similarities between different Diphyllobothrium tapeworms, species‐specific diagnosis is challenging (Chen et al., ). More recent studies have preliminarily identified two Diphyllobothrium specimens by conventional morphological methods, and the identity of species was then confirmed by a molecular approach involving the 18S rDNA partial sequence, complete sequences of ITSs and 5.8S rDNA, partial sequences of mitochondrial cox1, and the mitochondrial NADH dehydrogenase subunit 5 (nad5) (Guo et al., ). To date, no reports of serologic or coproantigenic diagnostics of diphyllobothriosis exist.…”
Section: Helminthsmentioning
confidence: 99%
“…Therefore, some cases of diphyllobothriosis reported in mainland China were probably caused by infections with D. nihonkaiense ; case-patient 12 ( 13 ) in this study is considered to have had such a case. However, a recent report stating that the causative species of 2 diphyllobothriosis cases in northeastern China was D. latum which suggests that D. latum is also indigenous to mainland China ( 14 ). …”
Section: The Studymentioning
confidence: 99%
“…In mainland China, 15 cases of diphyllobothriosis among humans have been reported since the first report in 1927 through 2012; the etiologic species was identified as D. latum by morphologic characteristics ( 11 – 13 ; Table) and molecular markers ( 14 , 15 ). No cases of diphyllobothriosis had been reported in large cities such as Beijing and Shanghai during 1954–2007 ( 11 ).…”
mentioning
confidence: 99%